PENTINGNYA MANAJEMEN SUMBER DAYA MANUSIA DALAM LEMBAGA PENDIDIKAN UNTUK MENINGKATKAN MUTU PENDIDIK - M., U. Pg. Fitra A.; Fetmawati, Fetmawati; Adam, Siska Yeni (Jurnal Manajemen Pendidikan, 2025)
The success of development is largely determined by the quality of human resources, both in the role of decision makers, policy makers, thinkers, planners, to technical implementers and development supervisors. This study aims to examine the importance of human resource management (HRM) in improving the quality of educators in educational institutions. Proper HRM management is considered to have a significant impact on the effectiveness of education, the quality of graduates, and the success of educational organizations as a whole. Using a literature study and content analysis approach, this article identifies the main functions of HRM, such as planning, organizing, directing, controlling, to development and dismissal. This study also reviews the objectives of HRM from personal, functional, organizational, to social dimensions, as well as HRM development strategies that focus on the formation of competent educators and maintaining teacher work effectiveness. The results of the study indicate that good HRM implementation is essential to answer the challenges of modern education and improve the quality of learning in educational institutions.